PENGGUNAAN MULTIMEDIA INTERAKTIF GUNA MENCIPTAKAN PEMBELAJARAN YANG INOVATIF DI SEKOLAH - Atmawarni UMA (Universitas Medan Area, 2012)
Teaching and learning interaction ins chools is an interactive activity and the various components to realize the achievement of learning objectives have been established in the learning planning, to get there, first it need to be understood about the meaning of the term learning, teaching and interaction. These three terms will lead to the definition of teaching and learning interaction. The utilization of information technology in the making and using of interactive multimedia in learning in school be judged very effective in supporting the learning materials delivery. The use of interactive multimedia in the learning in school is one of solution to relieve stiffness, saturation, and the vacuum of students in learning so many kinds of subject in school. By steps and the process of the use of the right interactive multimedia, using interactive multimedia as the messaging media will stimulate thought, feelings, concerns and wishes of student so as to encourage the learning process more interactive and communicative and can enhance students learning experiences become more concrete.